Is coracoclavicular ossification a complication or a good prognostic factor after surgical treatment of acromioclavicular joint injury? - ŞAHİN, KORAY; Ertogrul R.; KAPICIOĞLU, MEHMET; Sahin K.; BİLSEL, İSMAIL KEREM; Celik H.; KAPICIOĞLU M.; Ersen A.; Bilsel K. (My University, 2022)
© 2022Background: The purpose of this study was to investigate whether heterotopic ossification (HO) in the coracoclavicular (CC) space after surgical treatment of acromioclavicular joint (ACJ) injury is a complication or a sign of good prognosis. Methods: Fifty-nine consecutive patients who underwent CC reconstruction with or without augmentation of the ACJ for acute ACJ injuries were analyzed. Postoperative American Shoulder and Elbow Surgeons (ASES) score, Constant score (CS), subjective shoulder value (SSV), and visual analog scale (VAS) results were evaluated. For radiological evaluation, HO was evaluated, and CC distances were measured. Results: Fifty-one patients (11 women and 40 men; mean age, 36 years [range, 17-68 years]) were evaluated after a mean follow-up of 3 years (range, 2-8 years). The mean ASES score at the follow-up was 82.73 (range, 51.6-100), mean CS was 85 (range, 50-100), mean SSV was 80 (range, 40-100), and mean VAS was 1.9 (range, 0-5). It was observed that the clinical outcomes (ASES, CS, SSV, VAS) of patients who developed ossification in the CC space were better than those who did not although it was not statistically significant. No statistically significant differences were found in the clinical outcomes (ASES, CS, SSV, VAS) between patients who underwent CC reconstruction without augmentation of the ACJ and those who were combined (P > .05). Conclusion: HO in the CC space is a common finding following AC joint fixation injury. We suggest that HO is not a complication and might possibly have positive effects on clinical outcomes.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Orthopedics and Traumatology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; ORTOPEDİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; ORTHOPEDICS; Cerrahi; Ortopedi ve Spor Hekimliği; Surgery; Orthopedics and Sports Medicine; AC joint; Acromioclavicular joint dislocation; Arthroscopic fixation; Case Series; Coracoclavicular ligament surgery; Heterotopic ossification; Level IV; Shoulder injuries; Treatment Study